Identification and Valuation of Blue Economy Sectors in the Seribu Islands Regency Based on Economic, Social and Envorment Performance - Azka, Azka; Sahid Sujiwo, Aryo (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
Resources contained along the coast and ocean play a significant part in fostering regional economic growth. Therefore, for the benefit of the community, both now and in the future, marine and coastal regions must be protected and used efficiently. Developing the blue economy sector is one promising way to promote economic growth in coastal and marine regions. One issue coming up has to do with the blue economy's governance and sustainability performance. The purpose of this study is to measure the sustainability performance of the blue economy and to identify the sectors that require development. Furthermore, this study aims to develop a governance model for the blue economy based on the TBL concept. Untung Jawa Island, located in Seribu Islands Regency - DKI Jakarta Province is the study area. FGD, questionnaires, in-depth interviews, and field observations were among the methods used to collect data. In order to address the research issues, this study uses the Interpretive Structural Modeling (ISM) and Blue Economy Valuation Toolkit (BEVTK) methodologies. According to the findings, four sectors might be developed: i.e., ship docking, aquaculture, port and sea transportation, and marine tourism. In this instance, ship docking performs the best in terms of environmental sustainability, port and sea transportation concerning social sustainability, and marine tourism as regards economic sustainability. Additionally, it was discovered that six factors: i.e., central and regional government policies, law enforcement and regulations, socio-cultural policies, community leaderships, and economic capacity and viability are crucial to the growth of a sustainable blue economy.